Influence of Season and Soil Properties on Fungal Communities of Neighboring Climax Forests (Carpinus cordata and Fraxinus rhynchophylla) - Park, Ki Hyeong; Oh, Seung-Yoon; Yoo, Shinnam; Fong, Jonathan J.; Kim, Chang Sun; Jo, Jong Won; Lim, Young Woon (Frontiers in Microbiology, 2020)
Trees in forest ecosystems constantly interact with the soil fungal community, and this interaction plays a key role in nutrient cycling. The diversity of soil fungal communities is affected by both environmental factors and host tree species. We investigated the influence of both of these factors by examining the total fungal communities in the rhizospheric soil of climax tree species that have similar ecological roles (Carpinus cordata, an ectomycorrhizal [ECM] tree, and Fraxinus rhynchophylla, an arbuscular mycorrhizal [AM] tree) in temperate forests with continental climates of Mt. Jeombong, Republic of Korea. Fungal communities were assessed by Illumina-MiSeq sequencing the internal transcribed spacer (ITS) region of environmental DNA, and comparing their environmental factors (season and soil properties). We found that soil fungi of the two forest types differed in terms of community structure and ecological guild composition. The total fungal community composition changed significantly with seasons and soil properties in the F. rhynchophylla forest, but not in the C. cordata forest. However, potassium and carbon were significantly correlated with fungal diversity in both forests, and a positive correlation was found only between symbiotrophs of C. cordata and the C/N ratio. Thus, the effects of environmental factors on soil fungal communities depended on the host trees, but some factors were common in both forests. Our results indicate that individual tree species should be considered when anticipating how the fungal communities will respond to environmental change.